Gangland Chicago : criminality and lawlessness in the Windy City, 1837-1990 - Lindberg, Richard C., 1953- (Rowman & Littlefield, 2015)
Chicago and its history are defined by such notorious crime figures as Al Capone and John Dillinger. Gangland Chicago vividly recounts the evolution of street gangs in Chicago before Capone and Dillinger, and the rise of organized crime that earned the Windy City a reputation for unchecked violence, lawlessness, and mayhem.